Sikap Wanita Pekerja Pengrajin Batik terhadap Profesinya ditinjau Dari Keadaan Sosial Ekonomi di Sumberjambe Jember - Roro Aditya Novi Wardhani , Shendy Andrie Wijaya (Universitas PGRI Madiun, 2018)
The development program will be successful by improving the position of women in the community according to one millennium development with one of the indicators of achievement by 2015 promoting gender equality and women's empowerment and ensuring the sustainability of environmental functions. The extent to which such rights and obligations can be exercised by women is not only dependent on others but also on the nature of the dependence and independence of the woman herself. This study aims to analyze and know how the influence of socio-economic conditions on the attitudes of women workers to their profession as measured from the level of education, family income and burden of family dependents. The population in this study is all women batik craftsmen in Sumberjambe Village Jember. This research is explanatory research that is research to test the relation or influence between hypothesized variables. In this study there is clearly a hypothesis that will be tested the truth. Analyzer used is multiple linear regression analysis. The result of the analysis shows that the socio-economic condition influences the attitude of the batik craftsmen worker in Sumberjambe Village.